Prosthetic rehabilitation of a post evisceration patient with Non-Fabricated ocular prosthesis: A case report - Jaya Atmaja, Herman; Wahyuningtyas, Endang; Intan Ruspita (Indonesia Prosthodontic Association, 2024)
The disability associated with the loss of eye can cause significant physical and emotional problems in sufferers. Rehabilitation of patients with eyeball loss requires an eye prosthesis that can restore optimal cosmetic and psychological function. Eye prostheses can be made from non-fabricated acrylic resin. In this case report, a 23-year-old female patient came to the RSGM Prof. Soedomo, Faculty of Dentistry, Gadjah Mada University with complaints of missing left eye since 8 years ago with a diagnosis of phthisis bulbi. The results of the clinical examination showed that the conjunctiva was in good health and there was no infection. The treatment in this case was the manufacture of non-fabricated ocular prostheses made of acrylic resin. Custom-made ocular prostheses provide satisfactory results thereby improving psychology and emotional as well the social aspect.